Targeted Delivery of CRISPR/Cas9‐Mediated Cancer Gene Therapy via Liposome‐Templated Hydrogel Nanoparticles. (16th October 2017) - Chen, Zeming; Liu, Fuyao; Chen, Yanke; Liu, Jun; Wang, Xiaoying; Chen, Ann T.; Deng, Gang; Zhang, Hongyi; Liu, Jie; Hong, Zhangyong; Zhou, Jiangbing
Abstract: Due to its simplicity, versatility, and high efficiency, the clustered regularly interspaced short palindromic repeat (CRISPR)/Cas9 technology has emerged as one of the most promising approaches for treatment of a variety of genetic diseases, including human cancers. However, further translation of CRISPR/Cas9 for cancer gene therapy requires development of safe approaches for efficient, highly specific delivery of both Cas9 and single guide RNA to tumors. Here, novel core–shell nanostructure, liposome‐templated hydrogel nanoparticles (LHNPs) that are optimized for efficient codelivery of Cas9 protein and nucleic acids is reported. It is demonstrated that, when coupled with the minicircle DNA technology, LHNPs deliver CRISPR/Cas9 with efficiency greater than commercial agent Lipofectamine 2000 in cell culture and can be engineered for targeted inhibition of genes in tumors, including tumors the brain. When CRISPR/Cas9 targeting a model therapeutic gene, polo‐like kinase 1 (PLK1), is delivered, LHNPs effectively inhibit tumor growth and improve tumor‐bearing mouse survival. The results suggest LHNPs as versatile CRISPR/Cas9‐delivery tool that can be adapted for experimentally studying the biology of cancer as well as for clinically translating cancer gene therapy. Abstract : Clinical translation of CRISPR/Cas9 technology requires development of safe approaches for efficient delivery of Cas9 and guide RNA. Here, novel liposome‐templated hydrogel nanoparticles (LHNPs) optimized for codelivery of protein and nucleic acids are reported. It is demonstrated that when coupled with the minicircle technology, LHNPs deliver CRISPR/Cas9 with efficiency adequate for treatment of tumors within and outside of the brain.